LOW-SEISMICITY PRECURSORS OF LARGE EARTHQUAKES IN KAMCHATKA - Sobolev G.A.; Tyupkin Yu.S. (My University, 1997)
A technique is proposed for calculating a new predictive parameter, RTL. The technique was tested using observations of four large earthquakes in Kamchatka (M > 7). It was found that a seismic quiescence had taken place during a period of up to three years before all earthquakes in their epicentral areas and had been followed by 'foreshock' activation. The areas where the two precursory phases occurred were several times longer than the ruptures calculated from empirical relations between the source size and the magnitude (or energy class). They were as long as ~100 km for earthquakes of M > 7. The main shock occurred at the edge of the anomalous area. The anomalies of seismic quiescence and activation were especially distinct where seismicity was analyzed in a depth range of 30 to 100 km.